2014
DOI: 10.1063/1.4900540
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–solid phase transition of hydrogen and deuterium in silica aerogel

Abstract: Behavior of hydrogen isotopes confined in disordered low-density nanoporous solids remains essentially unknown. Here, we use relaxation calorimetry to study freezing and melting of H2 and D2 in an ∼85%-porous base-catalyzed silica aerogel. We find that liquid–solid transition temperatures of both isotopes inside the aerogel are depressed. The phase transition takes place over a wide temperature range of ∼4 K and non-trivially depends on the liquid filling fraction, reflecting the broad pore size distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Also shown are average depression temperatures of freezing of H 2 (⟨Δ T freeze ⟩). Data for controlled pore glass (CPG) powders and SiO 2 -340 sample are taken from refs and , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also shown are average depression temperatures of freezing of H 2 (⟨Δ T freeze ⟩). Data for controlled pore glass (CPG) powders and SiO 2 -340 sample are taken from refs and , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The H 2 gas used was obtained from Matheson Tri-Gas with a purity of ≳99.999% and natural isotopic content. The details of the custom-built apparatus and the measurement procedure can be found elsewhere. , In particular, the calorimeter was designed to minimize the contributions to the effective heat capacity from the addendum and from the heat of condensation of H 2 on cooling. , In all the cases, porous specimens were overfilled with H 2 prior to cooling in order to allow the crystallization front to invade the porous matrix from outside the monolith and, hence, to minimize possible kinetic undercooling events inside the porous matrix. The total amount of H 2 in the cell and the thermal link (Cu wires) between the calorimeter cell and the heat sink were selected so that the crystallization of H 2 took ≳3 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For 0-300 K temperature, an enhanced heat capacity of hydrogen inside a norbornene-based aerogel has been recently reported by the experimental works of Kucheyev and Lenhardt [14]. Cleve et al revealed the size and thermal effect on the effective heat capacity of hydrogen and deuterium entrapped in silica-aerogel [15]. However, none of the earlier researchers investigated the size dependency of the heat capacity of liquid argon under nanoscale confinement at different temperatures.…”
mentioning
confidence: 99%